Psychological distress and its associations with past events in pregnant women affected by armed conflict in Swat, Pakistan: a cross sectional study. Issue 1 (December 2015) - Khan, Muhammad; Chiumento, Anna; Dherani, Mukesh; Bristow, Katie; Sikander, Siham; Rahman, Atif
Abstract Background The public health significance of maternal mental health is well established. Armed conflicts expose populations to events that could have long-term negative consequences for mental health of pregnant women and their children. This study explores the prevalence and associated risk factors for psychological distress of women during pregnancy, including exposure to past conflict-related potentially traumatic events, in a population exposed to armed conflict in the Swat region of Pakistan. Methods A community-based cross-sectional survey of 349 pregnant women in two union councils in Swat was conducted. Psychological distress was measured using the Self-Reporting Questionnaire (SRQ). Conflict-related potentially traumatic events (PTEs) were measured through an adapted version of the Harvard Trauma Questionnaire. Information was also collected on major life events (Life Events Checklist), social support (Multidimensional Scale of Perceived Social Support), and demographic and socio-economic variables. Results Prevalence of current psychological distress was 38.1 % (95 % CI: 33.1, 43.3). Psychological distress was significantly associated with three or more potentially traumatic events (PTEs) experienced during the conflict (OR = 2.62, 95 % CI: 1.22, 5.61); three or more major life events in the year following the conflict (OR = 3.25, 95 % CI: 1.82, 5.82) and inversely associated with family support (OR = 0.91, 95 % CI: 0.88, 0.95). Conclusion This is one of the first community based cross sectional surveys in Swat valley, Pakistan to assess the prevalence of psychological distress during pregnancy in an area affected by conflict. Over a third of women show evidence of significant psychological distress. Exposure to potentially traumatic events remained independently associated with psychological distress 1 year after conflict ended, suggesting that conflict exposure may have long-term impacts upon maternal mental health. Combining this with findings relating to the cumulative impact of major life-events, and the protective factor of family support highlights the importance of developing culturally appropriate psychological interventions accessible to pregnant women rebuilding their lives following conflict.